The Feasibility Analysis of Layer Livestock Business in Alebo Village Konda District South Konawe Regency - Zaresta, Muhammad; Indarsyih, Yusna; Sadimantara, Fahria Nadiryati (International Journal of Agricultural Social Economics and Rural Development (Ijaserd), 2022)
This study aims to analyze the feasibility and sensitivity of laying hens in terms of financial aspects and if there is an increase in variable costs and a decrease in product prices. This research was conducted in Alebo Village, Konda District, South Konawe Regency, from September 2021 to January 2022. The object of this research is the Laying Chicken Livestock Business. This research uses the case study method. Research variables include respondent identity and business feasibility analysis. Analysis of the data used in the financial feasibility analysis includes the analysis of Net Present Value, Net Benefit-Cost Ratio Analysis, Internal Analysis of Return, Payback Period Analysis, and Sensitivity Analysis. The results of this study indicate that the financial aspect obtained an NPV value of IDR774.411.584, with a discount factor used of 15%, Net B/C of 2.32, IRR of 49%, the Payback period for two years four months so that the chicken farming business laying breeds are declared financially viable. Based on the sensitivity analysis, the business is still feasible to run despite an increase in the price of corn feed and DOC by 30% and a decrease in the selling price of eggs by 15%.